Long-term outcome of femoral derotation osteotomy in children with spastic diplegia - Dreher, Thomas; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Swartman, Benedict; Schuster, Waltraud; Gantz, Simone; Hagmann, Sébastien; Braatz, Frank (Gait & posture, 2012)
Satisfactory short-term results after femoral derotation osteotomy (FDO) for the treatment of internal rotation gait in cerebral palsy have been reported by various authors. However, there are only a few longer-term studies reporting results 5years after FDO and these are not in agreement. There are no reports on the clinical course beyond the pubertal growth spurt. 33 children with diplegia (n=59 legs, age: 10.5±3.6years) and internally rotated gait were examined pre- (E0), 1year (E1), 3±1 (E2) and 9±2 (E3)years after distal (27 legs) or proximal (32 legs) FDO as part of multilevel surgery, using standardized clinical exam and 3D gait-analysis at all examinations. The amount of intra-operative derotation averaged 25°. ANOVA was used for statistics (p<0.05). Mean hip internal rotation in stance at E0 of 17.3° was significantly changed to 1.0° of external rotation at E1 and was maintained at 4.2° at E3. The same clinical course was found for foot progression angle. The mid-point of passive hip rotation at E0 was 21°. This was significantly decreased to 6° at E1 and showed a small but significant increase reaching 12° at E3. The results of this study showed a good overall correction of internally rotated gait following FDO. These improvements were maintained at long-term follow-up after the pubertal growth spurt. Recurrence was observed in some cases with overall severe deterioration. In those patients persistent dynamic factors leading to recurrence should be further investigated.